Agency Conflict and Debt Maturity: The Role of Accrual Quality, Earnings Smoothing, and CEO Educational Background Diversity - Eka Rosalina (Ilomata International Journal of Tax and Accounting, 2026)
Debt maturity is a strategic financial decision that plays a crucial role in managing liquidity risk and maintaining a company's financial stability, particularly in emerging markets such as the Indonesia Stock Exchange. Drawing on agency theory and upper echelon theory, this study examines the relationship between financial reporting quality and managerial characteristics with corporate debt maturity. Debt maturity is defined as the proportion of short-term debt to total debt, with higher values indicating shorter debt maturity. This study uses panel data from 89 manufacturing companies listed on the stock exchange during the 2015–2025 period and employs a fixed-effects regression model. Accrual quality is measured using the modified Jones model, income smoothing is represented by earnings volatility, and CEO educational diversity is calculated using the Herfindahl–Hirschman Index. The results show that accrual quality has a negative and significant relationship with debt maturity, indicating that higher financial reporting quality is associated with a lower proportion of short-term debt. This finding suggests that increased transparency reduces information asymmetry and increases creditor confidence, thus reducing companies' reliance on short-term debt as a monitoring mechanism. Earning smoothing does not show a statistically significant relationship with debt maturity, indicating that the practice is not a primary consideration for creditors in determining a firm's debt maturity structure. Meanwhile, CEO educational diversity shows a significant relationship with debt maturity, suggesting that managerial characteristics may influence corporate financing decisions. Overall, these findings suggest that the quality of financial reporting and managerial influence play a significant role in determining a company's debt maturity policy, particularly in decisions about the use of short-term debt.